Circulating fatty acid profiles are associated with protein energy wasting in maintenance hemodialysis patients: a cross-sectional study - Khor, Ban Hock; Sahathevan, Sharmela; Sualeheen, Ayesha; Md Ali, Mohammad Syafiq; Narayanan, Sreelakshmi Sankara; Chinna, Karuthan; Abdul Gafor, Abdul Halim; Goh, Bak Leong; Ahmad, Ghazali; Morad, Zaki; Mat Daud, Zulfitri 'Azuan; Khosla, Pramod; et al. (Nature Research, 2021)
The metabolic impact of circulating fatty acids (FAs) in patients requiring hemodialysis (HD) is unknown. We investigated the associations between plasma triglyceride (TG) FAs and markers of inflammation, insulin resistance, nutritional status and body composition. Plasma TG-FAs were measured using gas chromatography in 341 patients on HD (age = 55.2 ± 14.0 years and 54.3% males). Cross-sectional associations of TG-FAs with 13 markers were examined using multivariate linear regression adjusted for potential confounders. Higher levels of TG saturated fatty acids were associated with greater body mass index (BMI, r = 0.230), waist circumference (r = 0.203), triceps skinfold (r = 0.197), fat tissue index (r = 0.150), serum insulin (r = 0.280), and homeostatic model assessment of insulin resistance (r = 0.276), but lower malnutrition inflammation score (MIS, r =  − 0.160). Greater TG monounsaturated fatty acid levels were associated with lower lean tissue index (r =  − 0.197) and serum albumin (r =  − 0.188), but higher MIS (r = 0.176). Higher levels of TG n-3 polyunsaturated fatty acids (PUFAs) were associated with lower MIS (r =  − 0.168) and interleukin-6 concentrations (r =  − 0.115). Higher levels of TG n-6 PUFAs were associated with lower BMI (r =  − 0.149) but greater serum albumin (r = 0.112). In conclusion, TG monounsaturated fatty acids were associated with poor nutritional status, while TG n-3 PUFAs were associated with good nutritional status. On the other hand, TG saturated fatty acids and TG n-6 PUFAs had both favorable and unfavorable associations with nutritional parameters.